Labour taxation and its impact on employment growth - Dolenc, Primož (Managing global transitions, 2012)
The paper aims to assess the characteristics of labour taxation for five different groups of workers and labour market performance (in terms of employment and unemployment rate) in the EU and to examine whether tax wedge affects employment growth in the EU. The descriptive empirical estimates show that the level of labour taxation varies greatly across EU Member States, by which the tax wedge tends to be higher among New Member States (excluding Cyprus and Malta). Furthermore, the panel regression analyses confirm statistically significant negative relationship between tax wedge and employment growth in the EU as a whole. Therefore, the empirical analysis suggests that the EU-27 should continue with the trend of reducing tax wedge, as this would have favourable effects on labour market performance, especially among New Member States.
Keywords: employment growth; trg dela; labour market; obdavčitev dela; rast zaposlenosti; economic policy; ekonomska politika; European Union; Evropska unija; labour taxation